Estuarine, Coastal and Shelf Science - Estuarine, Coastal and Shelf Science (Elsevier, 2026)
Estuarine, Coastal and Shelf Science is an international multidisciplinary journal devoted to the analysis of saline water phenomena ranging from the outer edge of the continental shelf to the upper limits of the tidal zone. Estuarine, Coastal and Shelf Science provides a unique forum, unifying the multidisciplinary approaches to the study of the oceanography of estuaries, coastal zones, and continental shelf seas. It features original research papers, review papers and short communications treating such disciplines as zoology, botany, geology, sedimentology, physical oceanography.
FI 0.93
Q1
Keywords: Life Sciences; Marine Biology; Acuerdos transformativos; Transformative agreements; Ecosistemas costeros; Estuarios; Oceanografía; Procesos marinos; Sedimentología; Dinámica costera